Labor Absorption in The Small and Micro Industries of Food and Beverages in Limpung Sub-District, Batang District (Business and Economic Analysis Journal, 2021)
Small and micro-processed food and beverage industry in Limpung District is one of the processing industries in Batang Regency. This makes researchers interested in conducting this research which aims to determine whether there is an effect of wages, production value and business age on labor absorption in small and micro-processed food and beverage industries in Limpung District. The problem in this research is whether the variable wages, production value and business age affect the absorption of labor in small and micro-processed food and beverage industries in Limpung District. This type of research uses a quantitative approach. The data of this study used primary data with 76 respondents, where the respondents were owners of small and micro food and beverage industries The data used is in the form of primary data taken by questionnaire method. Multiple regression analysis techniques using partial hypothesis testing (t test) and simultaneous hypothesis testing (F test) at the level of significance of 5%.Based on the research conclusions, wage, production value, and business age variables simultaneously (together) have a significant effect on the magnitude of the labor absorption variable.